Chemistry and Biology in the Biosynthesis and Action of Thyroid Hormones. Issue 27 (25th May 2016) - Mondal, Santanu; Raja, Karuppusamy; Schweizer, Ulrich; Mugesh, Govindasamy
Abstract: Thyroid hormones (THs) are secreted by the thyroid gland. They control lipid, carbohydrate, and protein metabolism, heart rate, neural development, as well as cardiovascular, renal, and brain functions. The thyroid gland mainly producesl ‐thyroxine (T4) as a prohormone, and 5′‐deiodination of T4 by iodothyronine deiodinases generates the nuclear receptor binding hormone T3. In this Review, we discuss the basic aspects of the chemistry and biology as well as recent advances in the biosynthesis of THs in the thyroid gland, plasma transport, and internalization of THs in their target organs, in addition to the deiodination and various other enzyme‐mediated metabolic pathways of THs. We also discuss thyroid hormone receptors and their mechanism of action to regulate gene expression, as well as various thyroid‐related disorders and the available treatments. Abstract : A picture of health : Thyroid hormones are essential to control body metabolism, heart rate, neural development, as well as cardiovascular, renal, and brain functions. This Review discusses the chemistry and biology involved in the biosynthesis, plasma transport, metabolic pathways, and receptor‐mediated action of thyroid hormones in relation to thyroid related disorders and their treatment.